CYSTIC FIBROSIS-RELATED DIABETES - Dana-Teodora Anton-Paduraru; Carmen Oltean; Maria-Liliana Iliescu; Ginel Baciu; Laura Mihaela Trandafir (Romanian Journal of Pediatrics, 2014)
Cystic fi brosis-related diabetes is an entity distinct from diabetes mellitus type 1 and 2, but with symptoms characteristic to them. Along with the extension of the life expectancy, the prevalence of diabetes increased in association with a more severe decline of the lung function and a poorer nutritional status in comparison to that of people with cystic fi brosis but without diabetes. The authors present current data regarding the prevalence and physiopathology of the disease, the clinical picture, and the useful examinations in establishing the diagnosis, the therapeutic possibilities and disease prognostic. We conclude that the early diagnosis and appropriate therapeutic interventions may diminish the negative impact of diabetes on the lung function and the nutritional status in cystic fi brosis.